Pengaruh Kualitas Layanan dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan Indihome - Putri Nurzhavira Gusti; Sri Setyo Iriani (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
The purpose of this paper is to determine the effect of service quality and customer satisfaction on customer loyalty Indihome. The research method used is field research. The questionnaires were processed based on previous research questionnaires that had been carried out related to this research variable. The main research target sample consisted of telecommunication service users (Indihome) as many as 143 respondents. Because the dependent variable in this study is influenced by several independent variables, to perform Multiple Linear Regression Analysis the researcher uses the SPSS version 22 application. Reliability tests and statistical analysis were carried out to confirm the validity and reliability of the scale and answer research questions. The findings imply that service quality and customer satisfaction have been shown to have a positive and significant effect on the level of loyalty displayed by customers through research, data analysis, and discussion of findings. The limitation of the research or its implication is that for a more holistic research approach to customer loyalty, further research can examine customer satisfaction as a mediating variable or Z and by using other variables such as purchasing decisions, brand equity, trust, and commitment. Originality is very important for telecommunications services like Indihome, to understand what drives customer loyalty. This study yields useful findings, which Indihome managers can benefit from, in their efforts to develop and implement successful customer loyalty strategies.